The Routledge Handbook of Sexuality in East Central Europe (Taylor & Francis, 2025)
This handbook provides an overview of scholarly research on sexuality in East Central Europe for both students and academics, focusing on the Czech Republic, Hungary, Poland, and Slovakia, from the late nineteenth century to the present. The collection is organized into eight sections covering major areas of research including non-normative sexualities; family, marriage, and kinship; race/ethnicity and nationalism; birth, health, and reproduction; religion; sex, work, and mobility; violence; and sex education. The chapters highlight the breadth and depth of current scholarship on the region, past and present. The contributions present cutting-edge research treating each of the East Central European countries on its own terms and contextualizing sexual meanings, practices, and dynamics in relation to the specific ways they have been shaped, experienced, represented, and contested in the lives of people across these territories. In doing so, the book underscores the differences in the region’s trajectories of sexuality and sexual politics from those of not only the West but also Russia/USSR and (former) Yugoslavia across the long twentieth century. Written by a multidisciplinary team of international experts, The Routledge Handbook of Sexuality in East Central Europe is an ideal resource for scholars of European history, gender studies, anthropology, and sociology.